Abundance estimate of striped dolphins (Stenella coeruleoalba) in the Pelagos Sanctuary (NW Mediterranean Sea) by means of line transect survey - Lauriano, Giancarlo; Panigada, Simone; Canneri , Roberta; Zeichen, Marta Manca; Notarbartolo-Di Sciara, Guiseppe (J. Cetacean Res. Manage., 2023)
To assess cetacean densities in the Pelagos Sanctuary for Mediterranean Marine Mammals, a Marine Protected Area (MPA) specifically designated to protect cetaceans, a survey was carried out in the Ligurian-Provencal Basin (NW Mediterranean) in August 2008. An area of 58,000 km2 was surveyed in eight days with equally spaced zigzag transects, covering 1,255 km in favourable conditions. Tracklines were designed using Distance 5.0 to allow for homogeneous coverage probability over the selected area. Fifty three sightings of four cetacean species were made: striped dolphins (n = 37), fin whales (n = 12), sperm whales (n = 3) and Cuvier’s beaked whales (n = 1). Estimates of abundance were obtained using Distance 5.0. The estimated dolphin abundance was 13,232 (CV = 35.55; 95% CI = 6,640–26,368), with a density of 0.23 individuals km–1 (CV = 35.55; 95% CI = 0.11–0.45). No fin whale abundance estimate was possible due to the small sample size. The point estimate of the 2008 striped dolphin abundance estimate was almost half of that of a survey conducted in 1992 by Forcada and colleagues (1995) in the same area with comparable effort, platform and methodology (25,614; CV = 25.3; 95% CI = 15,377–42,658); nevertheless, the difference was not statistically significant. These results strongly support the need for further systematic monitoring in the Sanctuary and in the surrounding areas, in order to assess striped dolphin abundance, spatial and temporal trends.